A Bolognese collector rediscovered: Count Ludovico Caprara (1621–1695) and the seventeenth-century art market. (27th November 2020) - Iseppi, Giulia
Abstract: This study concerns the discovery of a new figure in the field of seventeenth-century art collecting: Count Ludovico Caprara, a general under Ferdinand II de' Medici. Newly discovered archival documents reveal that the Caprara family had one of the richest collections of paintings in Bologna, displayed in a palace close to the Piazza Maggiore; most of these works, however, remain untraced. Ludovico collected more than a hundred canvases, mostly portraits of contemporary painters. The discovery of a purchase note and an inventory of the picture gallery have allowed the role of Ludovico in contemporary collecting and his contacts with personalities in the art market of Seicento Bologna to be established. An attempt is made here to identify several paintings by Giovanni Andrea Sirani, Francesco Gessi and others, and to clarify certain aspects of Ludovico's taste, especially his preference for the Bolognese school, despite spending his life at the Medici court.